ANALISIS IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMPERTAHANKAN DAN MENINGKATKAN JUMLAH NASABAH PEMBIAYAAN MITRAGUNA PADA BANK SYARIAH INDONESIA (BSI) KCP PULAU PUNJUNG - Fiki Pramita; Sandra Dewi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Bank Syariah Indonesia KCP Pulau Punjung is a sharia-based bank located in pulau punjung sub-district whose working area covers the Dharmasraya district. PT.Bank Syariah Indonesia KCP Pulau Punjung is not the only bank on pulau punjung and customer’knowledge of the new tecnology applied by Bank Syariah Indonesia KCP Pulau Punjung and ATM is often hampered by network problems. The purpose of this research is to find out how to apply Customer Relationship Management Implementation Analysis in maintaining and increasing the number of Mitraguna Financing customer and the obstacles in implementing Customer Relationship Management. This research is descriptive qualitative research. The subjects of this research were 4 BSI employes and 1 BSI customer. The data sources used are primary data and secondary data. The data collection mthods used are observation, interviews, and docomentation mhetods. The result of this reserch indicate that customer Relationship Management helps PT. Bank Syariah Indonesia KCP Pulau Punjung to improve good relation with increasing the number of Mitragu financing customer. The obstacle in implementing thisis that BSI cannot provide financing to ASN, PPPK, PNS if their salaries are notpayroll at BSI because the financing requirements at Mitaguna, the customer’s salary must be payroll at BSI